2023
DOI: 10.1017/s0029665123002197
|View full text |Cite
|
Sign up to set email alerts
|

Improving adolescents' dietary behaviours in the school-setting: challenges and opportunities

Abstract: Adolescence is a critical time of physical, psychological and social development, and thus, optimal nutritional intakes are required during this life stage. Despite this, adolescence is recognised as a period of nutritional vulnerability, with many reportedly failing to meet current dietary guidelines. The school-setting presents a favourable environment to intervene and promote positive dietary behaviours and is also inclusive regardless of socio-economic status. However, a lack of consensus exists on how bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 104 publications
1
1
0
Order By: Relevance
“…Overall, in line with a recent review (74), this qualitative study has identified various influential factors impacting adolescents' food choices in secondary school canteens, with many also acting as barriers to the selection of the healthier food items in this setting. Moreover, similar to previous research with key school stakeholders outside the United Kingdom (75,76).…”
Section: Discussionsupporting
confidence: 69%
“…Overall, in line with a recent review (74), this qualitative study has identified various influential factors impacting adolescents' food choices in secondary school canteens, with many also acting as barriers to the selection of the healthier food items in this setting. Moreover, similar to previous research with key school stakeholders outside the United Kingdom (75,76).…”
Section: Discussionsupporting
confidence: 69%
“…Mean scores were computed for each subscale, where higher scores indicated a greater frequency of the respective behavior. Selective eating was defined in this study as a positive response of "always" to at least one item on the selective eating behaviors questionnaire, aligning with previous research [34][35][36][37][38][39].…”
Section: Evaluation Of the Children's Selective Eating Habitsmentioning
confidence: 80%